2011
DOI: 10.1039/c1cy00029b
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent immobilization of asymmetric organocatalysts

Abstract: The immobilization of organocatalysts is one of the most explored approaches to overcome the limitations associated with organocatalytic systems such as high catalyst loading, difficult product separation and catalyst recycling. When compared with the commonly used covalent immobilization methods, which usually involve tedious synthetic manipulations, the non-covalent attachment of organocatalysts to supports offers facile and modular construction of immobilized chiral catalysts with maintained or even improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 147 publications
0
30
0
Order By: Relevance
“…Among the various catalysts for direct asymmetric aldol reaction, a series of organocatalysts derived from L‐proline are of particular significance. This is why many efforts have been made to modify the structure of L‐proline so as to improve selectivity and reusability, reduce load, and avoid the use of organic solvent . To overcome these drawbacks, researchers also have made attempts to graft organocatalysts with suitable supports .…”
Section: Introductionmentioning
confidence: 99%
“…Among the various catalysts for direct asymmetric aldol reaction, a series of organocatalysts derived from L‐proline are of particular significance. This is why many efforts have been made to modify the structure of L‐proline so as to improve selectivity and reusability, reduce load, and avoid the use of organic solvent . To overcome these drawbacks, researchers also have made attempts to graft organocatalysts with suitable supports .…”
Section: Introductionmentioning
confidence: 99%
“…Having shown the usefulness of C 2 ‐symmetric ligands ( 1a , b , c and 2a , b , c ) as excellent homogeneous organocatalysts in the conjugate 1,4‐Michael addition of carbonylic type of compounds to nitrolefin, we turned our attention to immobilizing these organocatalysts onto silica and exploring their catalytic properties. Heterogenized organocatalysts offer many advantages, such as, easy separation, recyclability, and pores on the silica surface which may mimic natural enzymes; for these reasons, immobilized chiral organocatalysts for asymmetric catalysis have attracted a great deal of attention …”
Section: Resultsmentioning
confidence: 99%
“…Heterogenized organocatalysts offer many advantages, such as, easy separation, recyclability, and pores on the silica surface which may mimic natural enzymes; for these reasons, immobilized chiral organocatalysts for asymmetric catalysis have attracted a great deal of attention. [40][41][42][43][44] Enantiopure organocatalysts (1a,b,c and 2a,b,c) were immobilized onto silica using 4-(ethylbenzene)sulfonylsilica gel to afford immobilized organocatalyst (5a,b,c and 6a,b,c) (Scheme 3) and tested for their catalytic properties in the conjugate carbonylic addition to βnitrostyrene. Surprisingly, the organocatalysts 1c and 2c, which behaved as excellent homogeneous catalysts (Entries 13 and 16), on immobilization (5c and 6c) led to low yields and racemic mixtures of the final product.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
“…Although bond strength in noncovalently supported catalyst is weak, the catalyst itself is directly used for immobilization without need for modification or synthetic steps required for covalent attachment to support. 271 Inclusion of (S)-proline derivatives with β-cyclodextrin is a useful method for noncovalently supported organocatalyst ( Figure 25). The Zhang group demonstrated that the β-cyclodextrin-immobilized catalyst 475 is prepared conveniently by simply heating (4S)-phenoxy-(S)-proline and β-cyclodextrin in ethanol water and by removal of the solvent.…”
Section: Noncovalently Supported Organocatalystsmentioning
confidence: 99%